The promotion of digital inclusion through MOOC design and use: a literature review - Balula, Ana (2016)
The use of Massive Open Online Courses (MOOCs) is being increasingly equated as a viable option by several educational shareholders in the scope of many scientific areas; nevertheless, research as to its potentialities in terms of digital (and consequently social) inclusion is still sparse and somehow atomised. Thus, this paper aims at putting forward the results of a thorough literature review focussed on the studies that bring together the concepts of MOOC and digital inclusion, published between January 2014 and January 2015. Thus, the main goal was to find out if there is evidence that MOOCS can be an important means for embracing digital inclusion, in particular, by promoting the development of soft skills (e.g., digital skills, communication skills, interaction skills). First and because the concept is becoming more and more polysemic (due to its manifold uses, theoretical frameworks, and application contexts), the MOOC’s main facets are depicted, considering its derivatives (e.g., cMOOC and xMOOC). Moreover, some critical aspects that stand out from the content analysis of the results of the literature review are also highlighted, namely as to: accessibility, employability and lifelong learning promoted through MOOC use. In general, results suggest that there is still a long way to go for MOOCs to fully address the digital inclusion challenge.